(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
يقوم هذا البحث على دراسة لغوية دلالية تحليلية، تتناول موضوعًا بارزًا احتوته صفحات (مثنوي) مولانا جلال الدِّين الرُّومي بأجزائه الستة، كان قد طرقه غيره من أسلافنا المبدعين. وبما أن البحث يطمح إلى الكشفَ عن دقائق دلالات قصص الحيوان في المثنوي، لم يكن بدّ من قراءة هذه الوثيقة الأدبية، في ضوء معطيات علم اللغة الحديث، كنظرية السياق وغيرها. وهذا يستوجب بالضرورة لمحة عن حياة مولانا رائد المحبّة الإلهية ومؤسس الصوفية في العالم الإسلامي، بغية فهم اتجاهاته الفكرية والفلسفية عمومًا، ونظرته إلى الإنسانية بوجه خاصّ تلك التي تختزن قدرًا هائلًا من صفاء التعبير الروحي، والدعوة إلى إعادة كرامة الإنسان التي سحقت، وإلى نبذ التعصّب، والتسامح، والحبّ على الرغم من الظروف القاهرة إذ ذاك. ولمّا كان مجال البحث ضيِّقًا لا يتّسع للوقوف على دلالات جميع قصص الحيوان في المثنوي، فقد اقتصر الحديث على قصّة (الأسد والوحوش) لأنها تُوَفّي بالغرض المنشود. This research is based on an analytical semantic approach dealing with an important topic that has ubiquitously appeared on the pages of all 6 vols. of Mawlana Jalaluddin al-Rumi’s Mathnawi; a topic that was dealt with by many creative authors before him. If the goal of this research is to explore the details of animal stories in, the issue becomes clearer through a re-reading of this literary document based on findings of modern linguistics and its theories, such as the theory of context, and others. This requires having a look at al- Rumi’s life in all circumstances, and the various events that went on, with the aim of understanding his intellectual tendencies which hold a lot of the imagery and the beliefs in his diary, in addition to his expressive style. Since the research cannot accommodate all animal stories found in Mathnawi, the topic is limited to the story of (the lion and the beasts) which satisfies the intended goal of this research.